Fungal biofilm associated with long-term central venous access device: Complications and therapeutic difficulties - Pérez-Lazo, Giancarlo (2018)
Fungal infections associated with biofilms in biomedical devices are refractory to antifungal treatment and usually require the timely removal of the device, as well as the administration of systemic antifungals. We present the case of a 36-year- old female patient who received pain therapy administered by a Port-A-Cath long-term central venous access device. She developed catheter-related candidemi a and endocarditis caused by Candida parapsilosis. The catheter had to be removed by thoracotomy due to persistent infection despite the systemic antifungal therapy. An extensive biofilm surrounding the catheter was observed and Candida parapsilosis was isolated. Six weeks of antifungal treatment with a favorable clinical evolution were completed.